'The Pawns That They Moved Here and There'? Microacts, Room for Manoeuvre, and Everyday Agency in the 1974 Cyprus Conflict. (April 2022) - Halstead, Huw
Oral testimonies from Greek Cypriots who lived through the Greek dictatorship's 1974 coup d'état on Cyprus and the subsequent Turkish invasion frequently present the narrators as mere pawns in a macro-scale historical drama, having little to no control over or understanding of the broader events unfolding around them. On one level, this rings true, as individual soldiers and civilians were rarely if ever able to dictate or perceive the broader trajectories of the conflict in which they found themselves. Yet this perspective belies the subtler reality that even in chaotic conditions and under deeply restricted circumstances people exercise agency and create spaces, however small, in which to operate as autonomous agents and to shape their own personal trajectories. Whilst they could not leave the chessboard, these 'pawns' actively moved themselves here and there, performing microacts that locally refracted official diktats and ideologies in mutable ways. Moreover, in the construction of their testimonies they assert further agency, assembling these microacts into meaningful narratives by placing them within broader historical frameworks.